2015
DOI: 10.1016/j.jdeveco.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing growth and the lives of Bangladeshi women

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(172 citation statements)
references
References 41 publications
7
158
0
7
Order By: Relevance
“…Jensen (2012) finds that giving young Indian women access to call center jobs causes them to delay marriage and reduce fertility. Heath and Mobarak (2014) find similar results when women in Bangladesh gain access to garment factory jobs; they also find that access to garment jobs increases girls' school enrollment. In the Indonesian context, Federman and Levine (2005) find some evidence that growth in manufacturing employment is associated with greater school enrollment and less labor force participation by teenage girls.…”
Section: Are Wage Jobs Better Jobs and Do Better Jobs Empower Women?mentioning
confidence: 57%
“…Jensen (2012) finds that giving young Indian women access to call center jobs causes them to delay marriage and reduce fertility. Heath and Mobarak (2014) find similar results when women in Bangladesh gain access to garment factory jobs; they also find that access to garment jobs increases girls' school enrollment. In the Indonesian context, Federman and Levine (2005) find some evidence that growth in manufacturing employment is associated with greater school enrollment and less labor force participation by teenage girls.…”
Section: Are Wage Jobs Better Jobs and Do Better Jobs Empower Women?mentioning
confidence: 57%
“…Unlike the Reform here, however, these effects may not have the same magnitude for older women. Similarly, Heath and Mobarak (2015), who document the impact of the multiplication of garment factories, find a small decrease of 0.23 percentage points over 6.4 years of the probability to have a first birth. 26…”
Section: Comparison With Identified Sources Of Fertility Changesmentioning
confidence: 98%
“…Empirical and experimental studies of developing countries have identified three broad factors that affect fertility: access to modern methods of contraception (Goldin and Katz 2002, Bailey 2006, Ashraf et al 2014, Miller and Babiarz 2016, electrification and diffusion of household appliances (Bailey and Collins 2011, Lewis 2013, Grimm et al 2015, and change in education supply or work opportunities (Breierova and Duflo 2004, Jensen 2012, Aaronson et al 2014, Duflo et al 2015, Heath and Mobarak 2015, Lavy and Zablotsky 2015.…”
mentioning
confidence: 99%
“…This heterogeneity is particularly important in the Bangladeshi context; as recent evidence indicates, export-driven growth in the country has resulted in increased female labor force participation (Heath and Mobarak 2015). Mobility across employment types may also differ by gender.…”
Section: Heterogeneity By Gendermentioning
confidence: 99%
“…Bangladesh presents an important context for examining the link between trade and informality: the economy has been transformed by growth in the export oriented ready-made garments industry (Heath and Mobarak 2015). At the same time, there has been little change in the share of formal employment during a period of substantial export growth.…”
Section: Introductionmentioning
confidence: 99%